Validation of sputum gram stain and culture for diagnosis of pneumonia in critically iii patient: a retrospective observational study - Rahayu, Rahayu; Masfiyah, Masfiyah; Intisari, Dewi; Putri, Indri Hapsari; Hibatullah, M. Adam (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2023)
Validation of culture results based on direct gram stain plays a vital role in differentiating pathogens' cause of infection or colonization in pneumonia cases. Our study aims to evaluate the validation of diagnostic microbiology based on gram stain and culture compared to chest radiography in critically ill patients with suspected pneumonia. This was a single-center retrospective data analysis in the Intensive Care Unit at Secondary Care Hospital in Central Java. The quality of sputum was determined by using a Modification Criteria of Bartlett and a Semi-Quantitative Score. The results of sputum culture with neutrophils count > 10 and bacterial count > 2 per field in Gram stain were considered the presumptive pathogen. Seventy sputum specimens were collected; however, only 58 were selected for further analysis in this study. In sputum specimens with Bartlett score +2 and Semi-Quantitave score 3 or 4, the chest x-ray results of all patients had positive infiltrates (100%). Diagnostics accuracy of the results of clinical microbiologist examination with chest X-ray had a sensitivity of 90%, specificity of 60.71 %, accuracy of 65.5%, a positive predictive value of 61.36%, a negative predictive value of 78.6%. It was concluded that validation of diagnostic microbiology based on gram stain and culture had susceptible and adequately specific results to differentiate between presumptive pathogens from colonization in pneumonia cases.